2010
DOI: 10.2166/wst.2010.308
|View full text |Cite
|
Sign up to set email alerts
|

Performance of pervious pavement parking bays storing rainwater in the north of Spain

Abstract: Pervious pavements are drainage techniques that improve urban water management in a sustainable manner. An experimental pervious pavement parking area has been constructed in the north of Spain (Santander), with the aim of harvesting good quality rainwater. Forty-five pervious pavement structures have been designed and constructed to measure stored water quantity and quality simultaneously. Ten of these structures are specifically constructed with different geotextile layers for improving water storage within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Figure 1 shows the general car park bay features and details of the manhole access for sampling. Each car park bay in the three experimental parking areas was designed and constructed in order to store stormwater separately (Gomez-Ullate et al (2010). This was achieved by tanking the bays individually using a waterproof bituminous membrane, protected from damage due to the sub-base aggregates with a geotextile.…”
Section: Research Methodology 21 Experimental Car Park Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the general car park bay features and details of the manhole access for sampling. Each car park bay in the three experimental parking areas was designed and constructed in order to store stormwater separately (Gomez-Ullate et al (2010). This was achieved by tanking the bays individually using a waterproof bituminous membrane, protected from damage due to the sub-base aggregates with a geotextile.…”
Section: Research Methodology 21 Experimental Car Park Featuresmentioning
confidence: 99%
“…Others including pH, Electric Conductivity (EC) and Dissolved Oxygen (DO) were chosen as they represent water quality parameters used in previous research (Gomez-Ullate et al 2010). Finally, Total Petroleum Hydrocarbons (TPH) were measured since they have been found to be one of the most common pollutants present in runoff (Horner et al, 1994).…”
Section: Methodology For Measuring Water Qualitymentioning
confidence: 99%
“…Different types of pervious pavements were tested in Northern Spain [33][34][35]. Pervious surface materials had a greater effect than the geotextile layer in terms of water quality improvements.…”
Section: Removal Of Suspended Solidsmentioning
confidence: 99%
“…PPS's efficiency as a tool for source control is due to its capability to infiltrate stormwater into hard surfaces and gradually attenuate it into the soil or a drainage outlet (Newman et al 2003). The PPS have been shown by previous studies to be capable of removing most stormwater pollutants especially hydrocarbons through filtration, sorption and biodegradation (Coupe 2004;Brattebo and Booth 2004;Newman et al 2006;Gomez-Ullate et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that the geotextile material is an important component of the PPS design which is effective in stormwater pollutant retention (e.g. by filtering out heavy metals and adsorbing hydrocarbons) and serves as the site for biodegradation process within the system (Pratt, 1995;Bond, 1999;Coupe 2004;Culleton et al 2005;Newman et al 2006;Nnadi 2009;Gomez-Ullate et al 2010) and hence must be incorporated in the design in order not to compromise the efficiency of the system.…”
Section: Introductionmentioning
confidence: 99%